The Influence of Parenting toward Religious Behavior and Study Result - Yulisna Yulisna; Hadi Arbiyanto; Munawar Rahmat (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2017)
The aim of this article is to present the results of research concerning empirical description of the parenting and its influences on religious behavior and students’ study results in the subject of PAI (Pendidikan Agama Islam/Islamic Education). The research method used is qualitative and quantitative methods. The population of the research is all students and their parents in the fifth grade of elementary school in one group of Pulau Kijang, in Reteh Subdistrict, Indragiri Hilir, Riau. The sampling used the technique of cluster sampling for 80 students and 80 parents. The results of the research show that the parenting determines the height and low of students’ religious behavior and PAI study results. Students who have high and average religious behavior are educated by the parents having the authoritative parenting, while the students having low religious behavior are those who are educated by authoritarian, authoritative, permissive, authoritarian-authoritative combination, and authoritative-permissive combination parentings. Meanwhile, students who have the high study results are educated by the parents having the authoritative parenting, while the students whose study results are average are educated by the authoritarian, authoritative, permissive, authoritarian-authoritative combination, and authoritative-permissive combination parentings.